A study of Nakornpathom red clay body for application in ceramic products - Sriprasertsuk, Sutthima; Daosukho, Saijit (Bulletin of Applied Sciences, 2023)
This research aimed to develop red clay body which was used for stoneware production in Nakornpathom province. The body should have high fired strength, closed to the body strength used in current stoneware production which would be strong enough for forming and handling. The research was carried out by a selection of raw materials: Nakornpathom red clay and Sieved-Nakornpathom red clay, compared the results with Chiangmai commercial clay. The clay slap was pressed into the square-shape mold and the green samples were then sintered at a range of 1005 to 1248 oC. Colour, phase information, chemical composition, flexural strength, hardness, water absorption, shrinkage and thermal expansion were determined. The results revealed that the properties of Nakornpathom red clay can be developed for use in the stoneware industry. The water absorption rate of Nakornpathom red clay was less than 3% when applying the appropriate firing temperature between 1105 to 1200 oC. After firing, Nakornpathom clay showed red brown in color (L* a* and b* values were 34.84 20.22 and 34.81, respectively) with water absorption rate of 0.00%. Nakornpathom red clay and Chiangmai commercial clay presented no difference phase composition which contain quartz, cristobalite, mullite and hematite. The flexural strength of Nakornpathom red clay was 39.08 N/mm2 which was higher than Chiangmai commercial clay (22.58 N/mm2). The thermal expansion coefficient of the clay body was slightly higher than W31 clear ceramic glaze. The glazing ceramic prototype made from Nakornpathom red clay showed high flexural strength with no visible crack.